Clinical spectrum associated with MOG autoimmunity in adults: significance of sharing rodent MOG epitopes - Sepúlveda, Maria; Armangue, Thaís; Martinez-Hernandez, Eugenia; Arrambide, Georgina; Sola-Valls, Nuria; Sabater, Lidia; Téllez, Nieves; Midaglia, Luciana; Ariño, Helena; Peschl, Patrick; Reindl, Markus; Rovira, Alex; et al. (Journal of neurology, 2016)
The aim of this study was to report the clinical spectrum associated with antibodies to myelin oligodendrocyte glycoprotein (MOG) in adult patients, and to assess whether phenotypic variants are dependent on recognition of rodent MOG epitopes. We retrospectively analyzed the features, course and outcome of 56 patients whose samples were investigated by brain tissue immunohistochemistry and cell-based assays using human and rodent MOG. The median age at symptom onset was 37 years (range 18–70); 35 patients (63 %) were female. After a median follow-up of 43 months (range 4–554), only 14 patients (25 %) developed a neuromyelitis optica spectrum disorder (NMOSD), 27 patients (47 %) retained the initial diagnosis of isolated optic neuritis, 7 (12 %) of longitudinally extensive transverse myelitis, and 2 (4 %) of acute disseminated encephalomyelitis; 6 patients (11 %) developed atypical demyelinating syndromes (4 had relapsing episodes of short myelitis lesions which in one occurred with optic neuritis; 1 had relapsing brainstem symptoms, and 1 relapsing demyelinating encephalomyelitis). The course was frequently associated with relapses (71 %) and good outcome. Twenty-seven patients (49 %) had antibodies that recognized rodent MOG epitopes, and 9 of them (16 %) showed a myelin staining pattern in rodent tissue. Only the myelin staining pattern was linked to NMOSD ( p = 0.005). In conclusion, MOG autoimmunity in adult patients associates with a clinical spectrum wider than the one expected for patients with suspected NMOSD and overall good outcome. Antibodies to rodent MOG epitopes do not associate with any phenotypic variant.